2019
DOI: 10.3390/life9010024
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Escherichia coli Giant Protoplasts to Their Original Form

Abstract: The spheroplasts and protoplasts of cell wall-deficient (CWD) bacteria are able to revert to their original cellular morphologies through the regeneration of their cell walls. However, whether this is true for giant protoplasts (GPs), which can be as large as 10 μm in diameter, is unknown. GPs can be prepared from various bacteria, including Escherichia coli and Bacillus subtilis, and also from fungi, through culture in the presence of inhibitors for cell wall synthesis or mitosis. In this report, we prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…DNA replication is essential for cell division in normally dividing bacterial cells (native forms) [ 1 ] and affects both cell morphology and cell division [ 2 4 ]. It has been reported that the bacterial chromosome DNA attaches to the plasma membrane [ 5 10 ] although cell division does not occur in bacterial protoplasts or spheroplasts in the presence of an inhibitor of peptidoglycan biosynthesis [ 11 14 ]; removal of the peptidoglycan synthetic inhibitor can induce recovery from Escherichia coli spheroplasts to their native forms [ 15 17 ]. However, spheroplasts can enlarge in Difco Marine Broth (DMB) containing a peptidoglycan biosynthesis inhibitor, for example, penicillin [ 18 21 ], and interestingly, DNA replication has been reported during protoplast or spheroplast enlargement [ 13 , 14 , 18 , 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…DNA replication is essential for cell division in normally dividing bacterial cells (native forms) [ 1 ] and affects both cell morphology and cell division [ 2 4 ]. It has been reported that the bacterial chromosome DNA attaches to the plasma membrane [ 5 10 ] although cell division does not occur in bacterial protoplasts or spheroplasts in the presence of an inhibitor of peptidoglycan biosynthesis [ 11 14 ]; removal of the peptidoglycan synthetic inhibitor can induce recovery from Escherichia coli spheroplasts to their native forms [ 15 17 ]. However, spheroplasts can enlarge in Difco Marine Broth (DMB) containing a peptidoglycan biosynthesis inhibitor, for example, penicillin [ 18 21 ], and interestingly, DNA replication has been reported during protoplast or spheroplast enlargement [ 13 , 14 , 18 , 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also explored the possibility of implementing more complex systems in a FRAD system: cell-free transcription and translation from single-molecule DNA (digital gene expression) was developed for highly accurate selection of clones encoding enzymes with enhanced catalytic activity . However, these methods still have limitations when one aims to avoid nonspecific interaction of molecules with device surfaces or to reconstitute more dynamic systems accompanying morphological changes in membranes, like fusion, fission, budding, or division …”
mentioning
confidence: 99%
“…30 However, these methods still have limitations when one aims to avoid nonspecific interaction of molecules with device surfaces or to reconstitute more dynamic systems accompanying morphological changes in membranes, like fusion, fission, budding, or division. 31 A simple and fundamental solution for these problems is to use monodisperse liposomes as the microreactors. This is because the lipid bilayer of the liposome has the ideal surface for most biomolecules to avoid nonspecific absorption.…”
mentioning
confidence: 99%